UMPSA collaborates with Alps Electric (M) Sdn. Bhd. - Siti Nur Azwin, Zulkapri (UMPSA, 2024)
PEKAN, 23 August 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to strengthen its cooperation with industry partners through the signing of a memorandum of understanding (MoU) between UMPSA and Alps Electric (M) Sdn. Bhd.